High-energy dual-energy computed tomography for the characterization of large and thick objects - Alix Sardet; Daniel Eck; Nicolas Estre; Frédéric Moutet; Emmanuel Payan; Cécilia Tarpau (e-Journal of Nondestructive Testing)
Usual computed tomography (CT) systems provide information on the layout and nature of materials composing an object. However, this information is limited to the apparent linear attenuation μ of the materials. To reach a more precise and accurate description, in the form of the effective atomic number Zeff and the electronic density ρe, dual-energy imaging can be used. Conventional dual-energy computed tomograohy (DECT) techniques are: (a) pre-processing dual-energy data sets and performing conventional CT reconstruction [1], (b) reconstruct dual-energy data sets and analyse the ratio of obtained linear attenuation coefficients [2, 3] and (c) reconstruct data sets after a decomposition on a material basis [4-6]. While the second technique is relatively convenient to set-up, it is not completely energy-independent. The third technique has proven rather efficient; however, it raises the question of the choice of material base used for decomposition. When inspecting complex objects composed of a large number of differents materials, this choice can be crucial. Therfore, this work focuses on extending the first technique to high energies, as it does not require any assumptions on the materials to be detected and takes into account beam-hardening effects through the system spectral response.